Student knowledge, appreciation and awareness on current islamic issues and shitte ideology and its relationship towards academic achievement / Raja Haniza Soffia Raja Hussin, Saripah Najuwa T.A Rahman and Ummi Nadhirah Firus - Raja Hussin, Raja Haniza Soffia; T.A Rahman, Saripah Najuwa; Firus, Ummi Nadhirah (2017)
The knowledge of current Islamic issues and Shiite ideology is an important thing in our life. Nowadays, the current Islamic issues and Shiite ideology has become widen in our country and some people were easily influenced by the ideology especially the stu- dents. The study was conducted to identify the significant effect of the student knowledge, appreciation and awareness on current Islamic issues and Shiite ideology on academic achievement. The factors involved in this study are student knowledge, appreciation, and awareness on current Islamic issues and Shiite ideology. A total of 192 respondents from 1793 students are selected based on the Raosoft calculated software. The data for this study are gathered by using self - administered questionnaire and were analyzed by using IBM Statistical Package for Social Science version 20 (SPSS 20.0). The findings and the results of the research are analyzed by using Logistic Regression. The overall findings of the study show that the student knowledge and awareness are significantly influence the academic achievement. It is recommended to Kolej Islam Antarabangsa Sultan Ismail Petra (KIAS) to provide more program about the current Islamic issues and Shiite ideol- ogy in order to raise their awareness on these issues since it becoming wider in Malaysia. This study also recommended Kolej Islam Antarabangsa Sultan Ismail Petra (KIAS) to provide the campaign that will increase the knowledge of religion among students which is more practicability in their life such as their social life